2022
DOI: 10.1038/s41598-022-15992-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of grain iron and zinc, and thousand kernel weight in wheat (Triticum aestivum L.) using genome-wide association study

Abstract: Genetic biofortification is recognized as a cost-effective and sustainable strategy to reduce micronutrient malnutrition. Genomic regions governing grain iron concentration (GFeC), grain zinc concentration (GZnC), and thousand kernel weight (TKW) were investigated in a set of 280 diverse bread wheat genotypes. The genome-wide association (GWAS) panel was genotyped using 35 K Axiom Array and phenotyped in five environments. The GWAS analysis showed a total of 17 Bonferroni-corrected marker-trait associations (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 87 publications
(127 reference statements)
6
15
0
Order By: Relevance
“…However, the correlation between TKW and all the three agro-morphological traits was significant and highly negative, except in Y3 for PH. Significant correlations found in this study have also been reported in earlier studies [ 23 , 42 ]. The positively associated traits (DH, DM, and PH) can be improved simultaneously; however, for the improvement of negatively associated traits, the adoption of suitable breeding-methods to break the undesirable linkages is envisaged.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the correlation between TKW and all the three agro-morphological traits was significant and highly negative, except in Y3 for PH. Significant correlations found in this study have also been reported in earlier studies [ 23 , 42 ]. The positively associated traits (DH, DM, and PH) can be improved simultaneously; however, for the improvement of negatively associated traits, the adoption of suitable breeding-methods to break the undesirable linkages is envisaged.…”
Section: Discussionsupporting
confidence: 91%
“…Eight QTLs were identified for TKW on the 3A, 4A, 5A, 5B, 6A, and 7D chromosomes. Previous reports also identified some QTLs on the same chromosomes: 3A [ 10 , 19 , 24 , 50 , 56 ], 4A [ 19 , 31 , 46 , 50 ], 5A [ 23 , 29 , 40 , 57 ], 5B [ 20 , 29 , 40 , 45 , 52 , 53 , 54 , 57 ], 6A [ 23 , 29 , 31 , 37 , 46 , 48 , 50 , 52 , 53 , 55 , 56 , 57 ], and 7D [ 29 , 31 , 40 , 50 ], at different positions. In addition, three previous reports, i.e., Gahlaut et al [ 19 ], Edae et al [ 46 ], and Ramya et al [ 27 ] identified a QTL at 73 cM, 72.4 cM, and 70 cM, respectively, on the 5B chromosome, which was similar to the QTL ( QTKW-5B ) identified in the present study at 70.5–73.5 cM, on the same chromosome.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…QTLs with large effects were detected on chromosomes 2B and 7B and are associated with transcription factors such as zinc finger motifs and metal ion binding protein (phosphatase), all of which has a role in the additional loading of Zn in wheat grains. Multiple studies have reported QTLs for high Zn and Fe concentrations on chromosomes 2A, 2B, 5A, and 7B ( Srinivasa et al, 2014 ; Alomari et al, 2018 ; Alomari et al, 2019 ; Krishnappa et al, 2022 ). Transfer of these QTLs through marker assisted breeding will certainly improve mineral concentrations in wheat grains.…”
Section: Breeding For Improved Grain Zinc and Iron Content In Wheatmentioning
confidence: 99%
“…Agronomic biofortification is based on optimized fertilizer applications, whereas genetic biofortification is based on traditional plant breeding and/or genetic engineering to improve nutrient concentrations ( Cakmak, 2008 ; Borrill et al., 2014 ). Out of these two strategies, genetic biofortification has been identified as an effective and affordable technique to enhance food nutrition content in a sustainable long-lasting way to combat mineral nutrition deficiencies ( Krishnappa et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%